Prognostic value of metastatic pattern in colorectal cancer: a multicenter retrospective analysis in a real-life cohort. (1st February 2021) - Rumpold, H.; Kirchweger, P.; Niedersüß-Beke, D.; Falch, D.; Wundsam, H.; Metz-Gercek, S.; Piringer, G.; Thaler, J.
Abstract: Background: Metastatic patterns have been linked with prognosis in colorectal cancer. We aim to determine the distribution of metastases, their dynamics during disease and their prognostic impact for specific clinical treatment scenarios (resection of metastasis and/or systemic treatment, best supportive care). Material and methods: 978 patients diagnosed with metastatic colorectal adenocarcinoma treated at three oncological centers from 2006 to 2018 were included. Overall survival was assessed depending on tumor load, distribution of metastases and treatment of the patients. Results: Most patients had single site metastasis ( n  = 684; 69.9%): 398 patients had liver ( n  = 398; 40.7%) and 103 patients had lung only metastasis (10.6%). The number of organs involved in metastases at diagnosis was highly prognostic (HR 0.77; CI 0.65, 0.90), whereas the additional gain of metastases during progression of the disease was not. The majority of patients (62.9–74.2%) with initial lung, liver or both metastases retained their initial metastatic status. In the overall population, lung only metastases were associated with the most favorable outcome (HR 0.64; CI 0.50, 0.81). This was also observed in patients receiving best supportive care (HR 0.45; CI 0.27, 0.75). Resection of lung only metastases resulted in longer median survival (102.2 months). A relevant survival difference in patients treated by systemic therapy alone was not observed. Lung only metastasis was associated with rectal cancer ( p  < .001) and RAS -mutation ( p  = .01); both, lung and liver metastasis were associated with time from diagnosis to first metastasis ( p  < .001). Conclusion: The number of organs involved in metastasis at diagnosis but not the total cumulative number of involved organs is of prognostic relevance in colorectal adenocarcinoma. This prognostic relevant initial metastasis distribution remains unchanged in the majority of patients during the disease. However, the prognostic impact of the metastatic pattern is potentially altered by treatment modality.